Strategic action for waste management in Manado City to prevent marine debris input to Manado Bay: a preliminary study - Ricky L. Rengkung; Jane M. Mamuaja; Veibe Warouw; Markus T. Lasut (Universitas Sam Ratulangi, 2022)
Marine debris has become a serious threat for the coastal and marine environment. Their presence can degrade the quality of marine environments and also has negative impact on several aspects of people lives especially public health and aesthetics. Several efforts have been made, both short (to mitigate the impacts) and long terms (to manage them properly) efforts. Strategic action in waste management is very important in order to manage marine debris in Manado City; this is the objective of the research. In order to achieve the objective, several aspects on situation and condition of marine debris in Manado Bay has been described, and this include composition and density of debris at the coastal area, the quantity of the debris, waste management on land, the status of public awareness, the impact and degradation of marine debris in nature, institutional regulation, and waste management and planning. These aspects were analyzed to identify strengths and weaknesses before strategic actions for management are developed. The results showed that the composition, density, and quantity of marine debris in Manado Bay increased from 2017 to 2019. Waste management on land has been going well, the government institutions dealing with waste have been adequately arranged. Five strategic actions for waste management in Manado City to prevent the input of the waste to Manado Bay are proposed, they are: a) encouraging people to reduce the use of plastic-based products; b) involving people and community institution in waste management on land; c) increasing the activities of the community and community institution in keeping the environment (river, beach) clean; d) inviting the community and community institutions in working together to develop action programs which will be implemented jointly; and e) improvising the waste management according to existing regulations which include marine debris in specific management target and also incorporating rivers and other areas in waste management according to regulation.